Analisis Kesulitan Belajar Siswa pada Pembelajaran Bahasa Indonesia Kelas Rendah di SD Negeri 17 Banyuasin III - Damayanti, Aldona; Hakim, Lukman; Hera, Treny (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the learning difficulties of students in low grade Indonesian learning, especially in the aspect of reading and writing in third grade of elementary school, totaling 18 people. The research method used is descriptive qualitative method. Data collection techniques used in this study were interviews, observation, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusions or data verification. From the results of the study, it can be concluded that the difficulty in learning Indonesian occurs because there are still students who are not fluent in reading which are categorized as slow learning, namely difficulties in the form of slow learning. Students' learning difficulties in the writing aspect are included in the Good Enough category with an average result of 68.48 while students' learningdifficulties in learning Indonesian in the reading aspect are also in the Good Enough categorywith an average result of 64.44.